The THE CORRELATION OF PRIMARY INSOMNIA WITH PAIN IN THE CERVICAL AND THORACOLUMBAR REGIONS IN UNDERGRADUATE MEDICAL STUDENTS OF THE FACULTY OF MEDICINE, UDAYANA UNIVERSITY, CLASS OF 2023 - Nirmala, Made Nilam Ray; ., Muliani; ., Yuliana; Wirata, Gede; Karmaya, I Nyoman Mangku (E-Jurnal Medika Udayana; Vol 13 No 12 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i12.P15, 2024)
Pain in the cervical and thoracolumbar regions is a common musculoskeletal system disorder experienced by most people. This issue is caused by a variety of factors, including primary insomnia. This sleep disorder is highly prevalent in Indonesia and can affect anyone, including students. The purpose of this research was to examine the correlation between primary insomnia and cervical and thoracolumbar pain in undergraduate students from Udayana University's Faculty of Medicine, Class of 2023. This is a descriptive analytical research conducted in a cross-sectional design. The research included 156 participants who met the inclusion and exclusion criteria. Samples were collected by filling a self-data questionnaire, the Insomnia Severity Index (ISI), and the Nordic Musculoskeletal Questionnaire (NMQ). The data will be processed and analyzed univariately and bivariately with Microsoft Excel 2016 and SPSS 25. This research was also approved by Udayana University's Faculty of Medicine Research Ethics Commission. In this research, r value = 0.245 and p-value = 0.002 were found in the analysis of the correlation between primary insomnia and upper neck pain, r value = 0.170 and p-value = 0.034 in the analysis of the correlation between insomnia and lower neck pain, r value = 0.285 and p-value = 0.000 in the analysis of the correlation between insomnia and back pain, and r value = 0.265 and p-value = 0.001 in the analysis of the correlation between primary insomnia and low back pain. According to these findings, there is a significant correlation between primary insomnia and cervical and thoracolumbar pain. Keywords: Primary Insomnia, Cervical Region Pain, Thoracolumbar Region Pain, Medical Students